Legal Politics in the Establishment of the Sultan Adam Law (Positivization of Islamic Law in the Banjar Kingdom) - Hidayati, Tri; Hidayatullah, Muhammad Syarif (AL-ISTINBATH : Jurnal Hukum Islam, 2021)
This study aims to determine the position and authority of Sultan Adam al-Watsiq Billah (1826-1857) in the formation of the Law of Sultan Adam 1835 and to describe the political aspects of law in the formation of the Law of Sultan Adam 1835. The method used is normative legal research with statutory, political, and socio-historical approaches. The results are first, Sultan Adam has authority as King and a religious leader in establishing Islamic law as the positive law of the Banjar kingdom in Sultan adam law. Second, the legal-political aspect in Sultan Adam Law is found in the purpose of its formation as stated in the preamble of the sultan adam law Martapura version. They were named, perfecting religion and i'tikad; maintaining the harmony of the unity, and guidelines for judges in deciding a case during their reign so that the people become good. As King and qadhi (judge), Sultan Adam used the religious and political approach through Sultan Adam Law when his political power weakened under Dutch rule. He has successfully applied it to the character of the Banjar Society, which is thick with Islamic (tradition), which is more obedient to religious leaders than rulers. The Banjar people still apply some of the Sultan Adam Law provisions to this day.